The reason and pragmatic knowledge: retrieving the integrative meaning [Articol] - Bogatu, Eugenia (UTM, 2022)
The article discusses the social responsibility of scientists in the context of practical work. Knowledge has a major role, both in the development of an individual and of society as a whole. Today's society is a society of knowledge. Knowledge cannot evolve separately from information. The amount and quality of information depends to a large extent on its processing by artificial intelligence. The involvement of knowledge in the field of artificial intelligence is not possible without critical thinking. A knowledge society is not perceived without the involvement of researchers. They are the ones who promote and develop scientific knowledge. This type of knowledge is found in all areas of society.
Motivul și cunoașterea pragmatică: recuperarea sensului integrativ
Keywords: pragmatic knowledge; meaning; understanding; critical thinking; cunoaștere pragmatică; raţiune; gândire critică